1999
DOI: 10.1046/j.1365-313x.1999.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis gene encoding a chloroplast‐targeted β‐amylase

Abstract: Summary β‐Amylase is one of the most abundant starch degrading activities found in leaves and other plant organs. Despite its abundance, most if not all of this activity has been reported to be extrachloroplastic and for this reason, it has been assumed that β‐amylases are not involved in the metabolism of chloroplast‐localized transitory leaf starch. However, we have identified a novel β‐amylase gene, designated ct‐Bmy, which is located on chromosome IV of Arabidopsis thaliana. Ct‐Bmy encodes a precursor prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
86
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 32 publications
1
86
0
3
Order By: Relevance
“…In addition, starch is localized to plastids, whereas most ␤-amylases lack chloroplast transit peptides (Kreis et al, 1987;Monroe et al, 1991;Yoshida and Nakamura, 1991). Although chloroplast-localized ␤-amylases have been identified (Lao et al, 1999), the majority of ␤-amylase activity is extrachloroplastic (Beck and Ziegler, 1989;Nakamura et al, 1991). For example, 80% of the amylase activity present in Arabidopsis rosette leaves is located outside of chloroplasts (Lin et al, 1988b).…”
mentioning
confidence: 99%
“…In addition, starch is localized to plastids, whereas most ␤-amylases lack chloroplast transit peptides (Kreis et al, 1987;Monroe et al, 1991;Yoshida and Nakamura, 1991). Although chloroplast-localized ␤-amylases have been identified (Lao et al, 1999), the majority of ␤-amylase activity is extrachloroplastic (Beck and Ziegler, 1989;Nakamura et al, 1991). For example, 80% of the amylase activity present in Arabidopsis rosette leaves is located outside of chloroplasts (Lin et al, 1988b).…”
mentioning
confidence: 99%
“…1). In Arabidopsis, AtBAM1 and AtBAM3 belonging to subfamily II target chloroplasts (Lao et al, 1999;Sparla et al, 2006). In addition, total β-amylase activity is signifi cantly reduced in leaves of Arabidopsis bam1 and bam3 mutants, and bam1 and bam3 double mutants have a severe starch-excess phenotype (Fulton et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, analyses of recombinant proteins expressed in E. coli revealed that AtBAM1, AtBAM2 and AtBAM3 have measurable β-amylase activity (Lao et al, 1999;Sparla et al, 2006;Fulton et al, 2008). On the other hand, AtBAM4 lacks β-amylase activity and amino acid residues of the key active site, despite the fact that the bam4 mutant has elevated leaf starch (Fulton et al, 2008;Li et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations